The Effectiveness of the Desa Cantik Program in Village Data Management - Isnaini, Kholishah; Khikmah, Laelatul (LPPM-ITEBA, 2025)
The Desa Cinta Statistik Program (Desa Cantik) is an initiative by the Badan Pusat Statistik (BPS) aimed at enhancing village capacity in statistical data management to support evidence-based development planning. This study aims to evaluate the effectiveness of the Desa Cantik program in Kendal Regency, focusing on the satisfaction levels of village statistical agents and village officials regarding program implementation, village participation, BPS involvement, as well as the roles of relevant agencies and students in this program. The method used is quantitative descriptive analysis with a saturated sampling technique, involving 25 respondents from five selected villages in the program. The study results indicate that more than 75% of respondents are satisfied with the program's implementation, village participation, and BPS support. However, some challenges remain in coordination and community engagement. Therefore, optimizing socialization and strengthening coordination among stakeholders is necessary to improve the program’s effectiveness in the future